Influence of expression and purification protocols on Gα biochemical activity: kinetics of plant and mammalian G protein cycles - Timothy E. Gookin; David Chakravorty; Sarah M. Assmann (Frontiers in Molecular Biosciences)
Heterotrimeric G proteins, composed of Gα, Gβ, and Gγ subunits, are a class of signal transduction complexes with broad roles in human health and agriculturally relevant plant physiological and developmental traits. In the classic paradigm, guanine nucleotide binding to the Gα subunit regulates the activation status of the complex. We sought to develop improved methods for heterologous expression and rapid purification of Gα subunits, initially targeting GPA1, the sole canonical Gα subunit of the model plant species, Arabidopsis thaliana. Compared to conventional methods, our expression methodology and rapid StrepII-tag mediated purification facilitates substantially higher yield, and isolation of protein with increased GTP binding and hydrolysis activities. Human GNAI1 purified using our approach displayed the expected binding and hydrolysis activities, indicating our protocol is applicable to mammalian Gα subunits, potentially including those for which purification of enzymatically active protein has been historically problematic. We subsequently utilized domain swaps of GPA1 and human GNAO1 to demonstrate that the inherent instability of GPA1 is a function of the interaction between the Ras and helical domains. Additionally, we found that GPA1-GNAO1 domain swaps partially uncouple the instability from the rapid nucleotide binding kinetics displayed by GPA1. In summary, our work provides insights into methods to optimally study heterotrimeric G proteins, and reveals roles of the helical domain in Gα kinetics and stability.